2019
DOI: 10.2147/idr.s211556
|View full text |Cite
|
Sign up to set email alerts
|

<p>Paradoxical Reaction In The Form Of New Pulmonary Mass During Anti-Tuberculosis Treatment: A Case Series And Literature Review</p>

Abstract: Introduction: Paradoxical reaction refers to deterioration of the original tuberculosis lesions or emergence of new infiltrative lesions during anti-tuberculosis treatment. The common manifestations of paradoxical reaction include new pleural effusion, cerebral tuberculosis and lymphadenitis. Paradoxical reaction manifested by new pulmonary mass is rare. Patients and methods: This article summarizes and analyzes the clinical manifestations, chest CT, laboratory findings, treatments, pathological biopsy results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Autoimmune inflammation in a large cavity might be related to a paradoxical reaction; only 1 patient with persistent severe inflammation in our study was identified as having a paradoxical reaction based on the worsening of existing disease or new TB lesions, with other diseases ruled out during antituberculous therapy. [ 15 ] Paradoxical reactions include recurring symptoms, such as fever, and radiological deterioration occurring from 1 week to several months after the initiation of antituberculous treatment. [ 15 ] Rapid killing of bacilli with antibiotics may lead to the release of large amounts of microbial components, which can stimulate a strong inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Autoimmune inflammation in a large cavity might be related to a paradoxical reaction; only 1 patient with persistent severe inflammation in our study was identified as having a paradoxical reaction based on the worsening of existing disease or new TB lesions, with other diseases ruled out during antituberculous therapy. [ 15 ] Paradoxical reactions include recurring symptoms, such as fever, and radiological deterioration occurring from 1 week to several months after the initiation of antituberculous treatment. [ 15 ] Rapid killing of bacilli with antibiotics may lead to the release of large amounts of microbial components, which can stimulate a strong inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Paradoxical reactions include recurring symptoms, such as fever, and radiological deterioration occurring from 1 week to several months after the initiation of antituberculous treatment. [ 15 ] Rapid killing of bacilli with antibiotics may lead to the release of large amounts of microbial components, which can stimulate a strong inflammatory response. [ 15 ] A previous report found a median CRP level of 4.5 mg/dL (IQR 2.8–7.4) in patients with paradoxical reactions, [ 16 ] for which steroid therapy is recommended for management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations